Sustainable Campus Through Organic Waste Management Program Implementation - Ellen J Kumaat; Indry S Manembu; Susan Marlein Mambu; Glanny M C Mangindaan (Journal of Sustainability Perspectives, 2023)
Implementing an organic waste management program is a crucial step in realizing a sustainable campus. Organic waste management such as yard waste management program in Sam Ratulangi University, Manado, is crucial to maintaining a sustainable environment. The university's efforts to implement sustainable waste management practices, such as recycling and create an alternative energy sources like biodigester, have significantly reduced the amount of waste sent to landfills and creates valuable resources such as heat and liquid organic fertilizer. The application of liquid organic fertilizer from a biodigester on the university's green house resulted in an increased Pakcoy growth parameters and productions. By using liquid organic fertilizer from a biodigester is a sustainable and effective way to fertilize green areas at Sam Ratulangi University. By implementing this practice, the university can reduce waste and support healthy plant growth while also promoting environmental stewardship.